(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: This article offers a relaxed, step-by-step look at plagiarism—what it is, why it matters, and how to steer clear of it without stress. It covers everything from really understanding sources to simple citation tricks and time-management hacks. Perfect for high-school or college students, bloggers, content creators, and anyone who writes at work or for fun. By the end, you’ll see that avoiding plagiarism is less about rigid rules and more about respecting ideas—both yours and others’—and building confidence in your own voice.